Spatial Distribution and Temporal Trends of Pneumonia in Indonesia: Descriptive Analysis of Early Warning and Response System (SKDR) Data, 2022-2024 - Wawang Wawang; Wahyono Tri Yunis Miko; Marisa Amelia (The Indonesian Journal of Infectious Diseases, 2025)
in Indonesia. This study aims to analyze the spatial distribution and temporal trends of pneumonia in Indonesia using data from the Early Warning and Response System (SKDR) for the period 2022–2024. Methods: This descriptive study utilized secondary aggregate data from the Indonesian Ministry of Health's SKDR, covering all 38 provinces from 2022 to 2024. Analyses were performed on the annual and cumulative distribution of pneumonia cases across provinces, visualized through ranking tables and choropleth maps, followed by a temporal analysis of quarterly trends Results: The SKDR recorded 1,204,023 pneumonia cases during the study period. Temporally, a significant yearly increase was observed, alongside a predictable seasonal pattern, with Quarter 2 consistently the period of lowest incidence. Spatially, extreme disparities were found, with the highest case hotspots concentrated predominantly on Java Island. Conversely, coldspots in Eastern Indonesia (e.g., Southwest Papua, Maluku) more likely reflect limitations in surveillance and healthcare access, indicating the presence of hidden high-risk areas. Conclusion:  Pneumonia in Indonesia exhibits dynamic temporal patterns and sharp spatial concentration. These findings underscore the necessity of differentiated control strategies: proactive interventions based on seasonal patterns, intensive resource allocation in hotspots to control transmission, and strengthened surveillance systems and healthcare access in coldspots to address hidden high-risk areas.